The Effect of the Government Internal Control System on Corruption Potential with Accountability as an InterveningVariable (Study on Regency/City Governments in Indonesia) - Finny Leonita Sari; Rindu Rika Gamayuni; Fajar Gustiawaty Dewi; Mega Metalia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to examine the relationship between the Internal Control System (SPI) and potential corruption with accountability as a mediating variable. The sample used in this study was local governments in Indonesia at the district/city level in 2020-2022 so that the sample amounted to 1,307 samples. The sample selection used purposive sampling technique and the analysis technique used was regression analysis and path analysis with SPSS 27 software. Furthermore, the sobel test was used to test the indirect effect of the independent variable on the dependent variable through the intervening variable. The results of the study provide empirical evidence that the SPIP variable has a negative effect on potential corruption. Then SPIP is also proven to have a positive and significant effect on accountability. And accountability has a negative and significant effect on potential corruption. And accountability acts as a mediating influence between SPIP on potential corruption.